Penggunaan Informasi Akuntansi untuk Memprediksi Return Saham: Studi terhadap perusahaan pemanufakturan dan nonpemanufakturan - Askam Tuasikal (The Indonesian Journal of Accounting Research, 2013)
A set of financial statements (i.e. balance sheet, income statement, statement of retained earnings, and statement of cash flows) is not completely useful for users until they analyze the information contents in the financial statements in the forms of ratios analyses. O’Connor (1973) shows that financial ratio have a weak predicting power for estimating stock returns. Ou and  Penman (1989) state that accounting information embodies fundamental information that is not captured by the market and reflected in stock prices. Machfoedz (1994) provides evidence that only several financial ratios are useful for predicting income no more than one year in advance. Zainuddin (1999) finds that certain financial ratios (some of which are used by Machfoedz) are not good predictors for estimating income growth one to two years foreward. The inconsistent results are due to the fact that dependent and independent variables are the outcomes of the same process (accounting process). These conflicting findings necessitate further investigation.The study examines whether financial accounting ratios are useful for predicting stock returns of manufacturing and nonmanufacturing companies one year to two years in advance. The contributions of this study are twofolds. First, the research provides valuable insights to investors  concerning the usefulness of financial accounting ratios. The ratios are used in predicting stock returns or abnormal returns. Second, this study enrichs literature topics in the area of financial accounting.The results indicate that for manufacturing companies financial ratios are not useful for predicting stock returns one year foreward. However, several ratios are useful for predicting stock returns two years foreward. For nonmanufacturing companies the results show that financial ratios are not useful for predicting stock returns either one year or two years foreward.Other findings indicate that predictive power for two years in advance of financial accounting ratios are different between manufacturing and nonmanufacturing companies.